Analysis of Determinants of MSMEs Performance in the Culinary Sector in Palembang City - Rina Tjandrakirana DP; Ubaidillah Ubaidillah; Ermadiani Ermadiani; Sri Maryati (Cita Konsultindo Research Center, 2023)
this study aims to analyze how the influence of the management control system, business strategy and information technology on the performance of Micro Small Medium Enteprise in the culinary sector in the city of Palembang. The population in this study were the culinary sector MSMEs in the city of Palembang, totaling 3,006 units. The sampling technique used a simple random sample (simple random sampling). while the determination of the sample used the slovin technique, and a sample of 97 MSMEs was obtained. The dependent variable in this study is company performance while the independent variables consist of three variables, namely Management Control Systems (MCS), Business Strategy, and Information Technology. The analysis technique used is the descriptive statistical test, validity test, reliability test, classical assumption test, multiple linear regression, and hypothesis testing